The Environment in the Fate of the Nomadic Civilization in the South of Russia in the Imperial and Soviet Periods. Review of the book: “Transformation of Nomadic Societies in the South of Russia in the Context of Natural and Climatic Factors (19th–mid-20th century)” / ed. E.N. Badmaeva. Rostov-on-Don: Altair Publishing House, 2024. 496 p. - E. U. Omakaeva (Nomadic Civilization: Historical Research)
The review discusses the main advantages of the collective monographic work, reveals its main content, indicating the relevance and debatability of the stated issues, as well as the practical value of the work (historical experience and modernity). The degree of compliance of the content with the stated goals and objectives, as well as the completeness and methods of their solution are analyzed. The extensive base of sources introduced into scientific circulation and used by the authors for a comparative analysis of statistical data revealing the dynamics of the transformation of nomadic societies is noted. The determining role of changes in the habitat, weather and climate factors, soil condition, vegetation and landscape as a whole is shown, which, of course, had a huge impact on the economic activity of nomads and the transition to sedentarism. The reviewer comes to the conclusion about the scientific significance of this work for the development of nomadology, for a more understanding of the mechanisms of transformations at various stages of the transformation of nomadic societies in the south of Russia, as well as a systemic rethinking of the motivation of the government policy carried out in the imperial and Soviet periods, and its effectiveness. The review also makes a number of recommendations.